Ethnomedicinal knowledge and novel folk claims from Sunderbani Block, Rajouri District, Jammu & Kashmir, India - Hussain, Jaffer; Tamchos, Sonam; Anjum, Talat; Shah, Aditya B.; Kumar, Gopesh; Nagayya, Shiddamallayya; Srikanth, Narayanam (Ecological Questions, 2025)
Medicinal plants have been essential to indigenous practices since ancient times. The Sunderbani region in Jammu and Kashmir (India) hosts a wealth of medicinal plants and traditional wisdom. However, these resources have faced threats due to socio-cultural changes, urbanization, and economic development, highlighting the need for conservation measures. Therefore, this study focuses on documenting the ethnobotanical knowledge of the study area. With prior consent, interviews and group discussions were conducted with traditional healers and locals to collect the data. The collected data were analysed using various quantitative indices. The study identified 66 plant taxa used to treat 12 ailment categories. Herbs constituted 45.45% of the plants, with leaves being the most frequently use plant part (40.5%). Asteraceae emerged as the dominant family. The majority of raw drugs were prepared as powders (32.5%). Prominent plants based on use report (UR) and use value (UV) included Terminalia bellirica (UR 51, UV 0.055), Phyllanthus emblica (UR 48, UV 0.052), Terminalia chebula (UR 47, UV 0.051), and Grewia optiva (UR 46, UV 0.050). Diseases of the circulatory system (ICD code 11) had the highest Informant Consensus Factor (ICF 0.97), while respiratory diseases (ICD code 12) had the lowest (ICF 0.15). Families like Phyllanthaceae (FUV 0.052) and Combretaceae (FUV 0.048) were highly cited. Many folk claims were novel and documented for the first time. The Sunderbani region is a repository of unique medicinal plants and traditional knowledge. Exploring the novel plant uses could serve as a lead for pharmacological research and future drug development while emphasizing the need for conservation efforts.